Statistical Analysis of Spending on Areas of Common EU Policy in Selected Euro Area Countries - Pawełek, Barbara; Kostrzewska, Jadwiga; Lipieta, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article presents results of taxonomic analysis of euro area countries belonging to the European Union in terms of similarity of the structure of spending on areas of common EU policy in 2000–2010. In a situation of global economic crisis strongly affects the euro area countries, special attention is devoted to such countries as Greece, Italy, Spain, Portugal and Ireland. As expected, Greece, Spain, Portugal and Ireland were characterized by a different level of spending on areas of common EU policy in 2000–2010 than the other euro area countries belonging to the EU. Exception was Italy, which showed a similarity in this respect to the other countries that joined the EU before 2004. The study used cluster analysis methods such as the method of Ward and k-means.